Analisa Kebulatan Permukaan Lubang Hasil Pembubutan Baja ST 41 dengan Metode Taguchi - Bagas Ramadhan Sutrisno; Pranowo Sidi; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
This journal is made to optimize a machine paramater on CNC turning steel of roundness hole surface. This turning technique that we use is boring by using carbide insert tool. The Parameter itself consists of Spindle Speed, Feed Rate and Depth of Cut. The material that use here is Steel 41 with 50 mm diameter, 30 mm length and 25 mm for diameter hole. Taguchi method has choosen to be used of this design experiment and also the calculation. To predict the optimum parameter on the roundness surface we use the Anova method on Software Minitab17. It will produce the optimum parameter that is Spindle Speed 900 rpm, Feed Rate 0,08 mm and the Depth of Cut 0,2 mm. Confirmation experiment is needed to prove that the prediction could produce the accuration of minimize the roundness surfaces value.